Analysis of Accounting Treatment of Receivables at LP3I College Bengkulu - Viana Dila; Sulisti Afriani; Nenden Restu Hidayah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This study aims to determine the suitability of presenting the accounting treatment of receivables at LP3I College Bengkulu. This type of research is qualitative descriptive, the data collection methods are direct observation, interviews, documentation, while the data analysis techniques used in qualitative descriptive analysis research are as a key instrument, data collection is carried out in a triangulation (combined) manner, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalization. The results of this research found that the presentation of the accounting treatment of receivables at LP3I College Bengkulu was still found to be lacking in several indicators that needed to be improved, namely 1.) income recognition: it would be better to follow Mulyadi's theory, because recognition at LP3I was not good or appropriate to use, 2.) allowance for losses on receivables: reserves for losses on receivables from LP3I were not carried out in a precise manner. inches in his recording, so it would be better to follow the theory according to Mulyadi.